Transformation of the [MnII2MnIII2(hmp)6]4+ Core into [CoIII2MnII2(hmp)6]4+ in the Reaction of the [Mn4(hmp)6(NO3)2(H2O)2] Cluster with [CoX4]2– (X = Cl, Br). Issue 32 (19th September 2013) - Kushch, Lyudmila A.; Yagubskii, Eduard B.; Simonov, Sergey V.; Shibaeva, Rimma P.; Suturina, Elizaveta A.; Gritsan, Nina P.; Sadakov, Andrei V.; Sulimenkov, Il'ya V.
Abstract: The reactions of [Mn4 (hmp)6 (NO3 )2 (H2 O)2 ](ClO4 )2 with (Bu4 N)2 [CoX4 ] (X = Cl, Br) in CH3 CN have been studied and the new heterometallic tetranuclear clusters [Co III 2 Mn II 2 (hmp)6 Cl2 (CH3 CN)2 ]Mn II Cl4 · 3CH3 CN and [Co III 2 Mn II 2 (hmp)6 Br2 (CH3 CN)2 ]Mn II Br4 · 4CH3 CN have been synthesized and characterized by TGA, electrospray ionization mass spectrometry, single‐crystal X‐ray diffraction, and magnetic measurements. The magnetic properties of the heterometallic clusters were analyzed by DFT and ab initio calculations. Abstract : The first heterometallic tetranuclear clusters containing a [Co III 2 Mn II 2 ] core have been synthesized and fully characterized. The magnetic susceptibility measurements in the temperature range 4–300 K reveal a rather strong intracluster antiferromagnetic coupling between the oxo‐bridged Mn II ions, in agreement with the results of DFT and ab initio calculations.